KOMPARASI KEMAMPUAN PEMAHAMAN KONSEP SISWA DENGAN BERBANTUAN ALAT PERAGA DAN VIDEO JAM SUDUT - Diah Ayu Sulistiani; Venissa Dian Mawarsari; Dwi Sulistyaningsih (Journal of Lesson Study in Teacher Education, 2023)
This study aims to determine the differences in students' conceptual understanding skills using the corner clock teaching aid and the corner clock demonstration video media in class IV MI Negeri 1 Pati. This research is an experimental research with a quantitative method approach. The result of this study is that there is a significant difference in students' conceptual understanding skills between those who use the corner clock teaching aid and the corner clock demonstration video on the Angle Measurement material for class IV MI Negeri 1 Pati. The ability to understand concepts of students who use visual aids is higher than students who use video clock corners, as evidenced by the average value of the increase in the first experimental class by 0.67 and the second experimental class by 0.58.